The Determinant of Stunting Prevalence in 24-59 Month Children in Hayahaya Village, Western Limboto Sub-district, Gorontalo Regency - Zakaria, Rabia; Suma, Juwita (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2020)
Background: Stunting is among the nutritional problems that lead to deficits in the children